The first exception: the obelisk in memory of Napoleonic prisoners on the island of Cabrera (1847, Spain) - Alberto Cañas de Pablos (Built Heritage)
Abstract Wars have been frequently commemorated in public space. In Spain, the Peninsular War has become key for memory policies almost since its beginning. More than 370 monuments from that period still stand today. Most of these monuments recall heroic achievements by Spanish men or regiments, but some (more than twenty) provide reminders of the occupying troops coming from France. The most important of these is the obelisk built in Cabrera, in the Balearic archipelago, where many prisoners, who had been defeated in Bailén (1808), were taken. Many of those soldiers died and/or suffered several illnesses there, prompting the Prince of Joinville to commission a monument there in their memory. Although there Swiss, German, Polish and Italian soldiers were also present, only the French are engraved in the stone. Primary and secondary sources have been used to complete this research. Despite the difficult place of the monument and the limited number of recent studies, this paper studies and analyses the process that led to this memory antenna.